Succinic acid as a coordination modulator for DMSO-free low-dimensional red-emitting tin perovskites - Akhil Sreevalsan; Woo Hyeon Jeong; Yifan Yu; Cheong Beom Lee; Gunhee Kim; Jongbeom Kim; Hochan Song; Hong In Jeong; Gyeong Eun Seok; Dong-Won Kang; Myoung Hoon Song; Kyeounghak Kim; et al. (Chemical Engineering Journal, 2026)

Development of Korea Air quality observation-based Box model (KAB) - Haeju Lee; Na-Hyeon Kim; Seonghui Lim; Minjoong J. Kim; Minseung Yeo; Min Young Kim; Taehyeon Kim; Ho-Jin Lim; Chang Hoon Jung; Ji Yi Lee; In Ho Song; Gookyoung Heo; et al. (Atmospheric Environment, 2026)

Quadruple co-infection with Mycobacterium tuberculosis complex and M. kansasii in a chronically immunosuppressed cat - Sungyoung Choi; Soo-Nyun Choi; Tak Gyeom Lee; Sungweon Ryoo; Ji-Hoon Kwak; Kun-Woo Kim; Tae In Park; Woo-Jin Song; Eun-Joo Lee; Kyu-Shik Jeong (Veterinary Research Communications, 2026)

Single-step-patterned dual-subpixel architecture for full-color QLED displays - Hyo-Bin Kim; Seong-Kuk Park; Jae-In Yoo; Sang Min Won; Jang-Kun Song (Chemical Engineering Journal, 2026)

Inkjet-printed full-color tandem quantum dot light-emitting diode with dual-color subpixels - Young-Jae Ko; Gyu-jin Shin; Hyo-Bin Kim; Seung-Ah Lee; Jae-In Yoo; Jun Hyup Lee; Jang-Kun Song (Chemical Engineering Journal, 2026)

Interaction of SFPQ with S100A8 and S100A9 in EoL-1 and EoL-1-IR cells - Jae Ha Baek; Geunyeong Kim; Yujin Hong; Min Hwa Hong; Ji-Sook Lee; Ik-Chan Song; Soo-Jung Gong; In Sik Kim (Molecular & Cellular Toxicology, 2026)

Characterisation and mechanism of action of the antimicrobial activity of hetero-exopolysaccharide from Lentilactobacillus buchneri KU200793 against Staphylococcus aureus and Listeria monocytogenes - Manoj Kumar Yadav; Ji Hoon Song; Robie Vasquez; Jae Seung Lee; Young-Seo Park; Hyun-Dong Paik; In Ho Kim; Dae-Kyung Kang (Archives of Microbiology, 2026)

A Fucose-containing Hetero-exopolysaccharide From Levilactobacillus brevis B151 Exhibits Potent Antimicrobial, Antibiofilm, and Antioxidant Activities - Manoj Kumar Yadav; Remilyn M. Mendoza; Ji Hoon Song; Robie Vasquez; Jae Seung Lee; Yeong-Seo Park; Hyun-Dong Paik; In Ho Kim; Dae‑Kyung Kang (Probiotics and Antimicrobial Proteins, 2026)

Corrigendum to ‘Comparative evaluation of surface-level PM2.5 modeling across Northeast Asia: relevance for regulatory and scientific applications’ [Environ. Pollut. 377 (2025) 126428] - Hyeon-Kook Kim; EunRyoung Kim; Chang-Keun Song; Jae-Ho Choi; Ganghan Kim; Myong-In Lee; Yujin J. Oak; Rokjin J. Park; Ilhan Ryoo; Seung-Muk Yi; Kyung-Mi Lee; Hyeok-Gi Cheo; et al. (Environmental Pollution, 2026)

Hydramethylnon-induced autophagy and apoptosis in human bronchial epithelial cells by homeostatic changes - Yeon-Ho Kang; Sou Hyun Kim; Hye-Jin Jeong; Ah-Yoon Song; Hye-In Park; Eun-Hye Kim; Young-Suk Jung; Yong Joo Park (Toxicology, 2026)

Estimation of radiogenic heat production rate of deep subsurface rock mass using natural gamma-ray logs - Yeonguk Jo; Myungsun Kim; Yoonho Song; Tae Jong Lee; In-Hwa Park; Changhyun Lee; Eui-Seob Park (Geosciences Journal, 2026)

Biocontrol potential of beauvericin produced in a submerged culture of Beauveria bassiana 331R against cotton aphid Aphis gossypii - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Hyunbok Song; Seulki Kim; Tae Young Shin; Taek Su Shin; Soo‑Dong Woo; Hae Woong Park (BioControl, 2026)

Comprehensive site screening and selection for offshore CO2 storage in the Early Miocene formations of the eastern Gunsan Basin, Yellow Sea - Kyoung-Jin Kim; Moohee Kang; Snons Cheong; Kue-Young Kim; In-Sun Song; Kwanghyun Kim (Marine and Petroleum Geology, 2026)

Ferroptotic stress-guided glutathione dynamics profiling identifies melatonin priming as a potential mesenchymal stem cell strategy for asthma therapy - Hyun Jun Im; Seok Woo Ha; Keunhong Jeong; Jinwon Lee; Chae-Min Ryu; Hyungu Kwon; Jihye Kim; Yi-Xi Gong; HongDuck Yun; YongHwan Kim; Ji-Woong Shin; Hye-Mi Kim; et al. (Chemical Engineering Journal, 2026)

Development and validation of a portable TDLAS system for gas chromatography–level quantification of methane emissions from rice - Sujeevan Rajendran; Wonbok Lee; Sun Hwa Lee; Dongjin Shin; Da Hee Jung; Yu Mi Kang; Seok-in Yun; Byoung Il Je; Chul Min Kim; Young Hun Song (Plant Biotechnology Reports, 2025)
Rice cultivation is a significant source of agricultural methane (CH₄), yet routine quantification still relies heavily on gas chromatography (GC), which limits throughput and field deployment. Here, we evaluated a portable tunable-diode-laser absorption spectroscopy (TDLAS) detector (PMD) as an alternative to GC for measuring CH₄ released from pot-grown rice plants under field conditions. Weekly closed-chamber samples from five cultivars were analyzed in parallel by GC (FID/MS) and the PMD. Standard gas tests showed an excellent linear relationship for the PMD (R 2 = 0.9995), indicating a near-ideal response. Across field samples, GC and PMD were strongly associated (R 2 = 0.9943). Bland–Altman analysis revealed a mean bias (GC − PMD) of 8.55 with 95% limits of agreement − 9.16 to 26.26, and Lin’s concordance correlation coefficient was 0.991, evidencing near-perfect agreement despite a slight systematic offset. A simple calibration with a linear regression eliminated the bias and narrowed the limits of agreement, while preserving the high correlation. Residual analyses suggested a modest influence of CO₂ (but not N₂O) on between-method differences. Taken together, the PMD provides rapid, robust, and labor-efficient CH₄ measurements that closely match GC when a fixed calibration is applied, enabling high-throughput phenotyping of rice genotypes and management practices in both laboratory and field settings. This calibrated, portable approach lowers barriers to large-scale screening for low-emission rice, supporting climate-smart crop improvement.

Genetic mapping of tomato mutants using InDel markers between S. pimpinellifolium and two S. lycopersicum cultivars - Smita Mirsyad Warsadiharja; Shandra Amarillis; Jung Heo; Seunghye Park; Hye-yeong Kang; Yong Jun Kim; Junwoo Lee; Kang Il Cha; Eun Song Lee; Ji In Jang; A-ra Joh; Keunhwa Kim; et al. (Plant Biotechnology Reports, 2025)

Effects of web-based behavioral intervention on fine particulate matter, pulmonary function, and airway inflammation in children: The COCOA randomized controlled trial - Dirga Kumar Lamichhane; Bo-Mee Kim; Jungyun Bae; Hea Young Oh; Dong In Suh; Youn Ho Shin; Kyung Won Kim; Kangmo Ahn; Hyo-Bin Kim; Song-I Yang; So-Yeon Lee; Soo-Jong Hong; et al. (Environmental Research, 2025)

Hybrid W-MgF2/graphene photothermal membrane for efficient solar-driven desalination - Ga Eun Lee; Jinsoo Cho; In-Young Jung; Da Seul Kim; Seok Joon Kwon; Won Jun Choi; Kyung Guen Song; Hak Ki Yu; Jeong Min Baik (Desalination, 2025)

Development of a feedback-regulated temperature control system to enable supercooling reversion in beef preservation - Seokhyeon Yun; Taeho Kim; In-U Jeong; Song-Yi Choi; Soyeon Kim; Jin Hong Mok; Taiyoung Kang (Innovative Food Science & Emerging Technologies, 2025)

High-purity Li₆PS₅Cl sulfide solid electrolytes via liquid-phase method synthesis for high-performance all-solid-state Li-ion batteries: Particle-scale analysis of formation with precursor and solvent optimization - Hyewon Jo; Bitna Kim; Byeong-Min Ahn; Youngjun Huh; Soyoung Kim; Jung Han Kim; Heetaek Park; Jun-Woo Park; Yoon-Cheol Ha; Jay Hyok Song; Je In Lee; Jun-Ho Park (Chemical Engineering Journal, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Comparative evaluation of surface-level PM2.5 modeling across Northeast Asia: relevance for regulatory and scientific applications - Hyeon-Kook Kim; EunRyoung Kim; Chang-Keun Song; Jae-Ho Choi; Ganghan Kim; Myong-In Lee; Yujin J. Oak; Rokjin J. Park; Ilhan Ryoo; Seung-Muk Yi; Kyung-Mi Lee; Hyeok-Gi Cheo; et al. (Environmental Pollution, 2025)

Multi-Enzyme Supplementation to Diets Containing 2 Protein Levels Affects Intramuscular Fat Content in Muscle and Modulates Cecal Microflora Without Affecting the Growth Performance of Finishing Pigs - Qianqian Zhang; Sungbo Cho; Junho Song; Jinuk Jeong; Minjae Yu; Seyoung Mun; Kyudong Han; In Ho Kim (Probiotics and Antimicrobial Proteins, 2025)

Correction to: PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2025)

Contribution of silicate fertilizer application to reducing CH4 emission and increasing productivity in Korean rice paddies - Snowie Jane C. Galgo; Sang Yoon Kim; Taek-Keun Oh; Hyon Chol Park; Ronley C. Canatoy; Keon Mok Sohn; In Bang Song; Pil Joo Kim (Field Crops Research, 2025)

Salinity alternation with dark treatment enhances the gel quality and quantity of carrageenan in a red alga, Chondrus crispus - Hye-In Song; Ji-Sook Park; Jang K. Kim (Aquaculture, 2025)

Transparent and visible light-activated antimicrobial air filters from electrospun crystal violet-embedded polyacrylonitrile nanofibers - Seung Yeon Lee; Jae Hak Shin; In Ho Kim; Dong Yun Choi; Dong Uk Lee; Gi Byoung Hwang; Bangwoo Han; Sang Bok Kim; Dong-Keun Song; Inyong Park; Jae Hee Jung (Environmental Research, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

Process modeling and assessment of waste polystyrene pyrolysis: Comparing catalytic and thermal methods - Jisoo Kim; Gwang-Nam Yun; In-Hyoup Song; Kwang Ho Song; Seung-Jun Baek; Jihoon Kim; Dong Won Hwang; Jinjoo An; Juwon Min (Chemical Engineering Journal, 2025)

Helical donor–acceptor bulk heterojunctions for dissymmetric circularly polarized light detection - Inho Song; Jaeyong Ahn; Sang Hyuk Lee; Sangwook Lee; Seoyoung Kim; Ye In Cho; Joon Hak Oh (Chemical Engineering Journal, 2025)

Maximum depositional age of the sedimentary succession in the southwestern margin of the Ulleung Basin from zircon age dating of conventional drilling cores - Hyun Suk Lee; Junghee Son; Gihun Song; Juhyeon Oh; Yoonsup Kim; In-Gul Hwang; Sehyun Kim; Wonjun Kwak (Geosciences Journal, 2025)
Biostratigraphic research has been conducted over the last four decades in the southwestern Ulleung Basin and has provided a chronostratigraphic framework to understand basin evolution. However, absolute geologic ages for the basin are almost absent owing to the lack of deep-drilled cores. To obtain the absolute age from the zircon, we extensively sampled and measured five deep-drilled conventional cores previously obtained for hydrocarbon exploration from the southwestern shelf of the Ulleung Basin. Maximum Depositional Ages (MDAs) for each cored interval are determined by the youngest age groups of zircons and are calculated to 12.1 ± 0.1 Ma for Gorae I-1, 12.9 ± 0.2 for Gorae I-2, 10.2 ± 0.8 for Gorae V-3, 11.4 ± 0.7 for Gorae V-4, and 16.9 ± 0.3 for Dolgorae V-1. All age groups exhibited relatively narrow errors (avg. ± 0.4 Ma), indicating good accuracy of MDA. The MDAs for the cores were first obtained by Laser Ablation-Multi Collector-Inductively Coupled Plasma Mass Spectrometry (LA-MC-ICPMS), and the youngest zircon grains were subsequently reanalyzed by Sensitive High-Resolution Ion Microprobe (SHRIMP) to prevent age underestimation due to possible Pb loss. The differences in absolute ages of Gorae I-1 and I-2 between LA-MC-ICPMS and SHRIMP methods are below than 0.8 Ma, indicating good verification of MDAs. The four seismic horizons that overlapped with the cored interval were newly established as GR I-2 MDA, GR I-1 MDA, GR V-4 MDA, and GR V-3 MDA (except for Dolgorae V-1 because of the poor quality of the seismic profiles). The newly defined MDA horizons were compared to the biostratigraphic sequence boundaries of (Yi et al., Marine and Petroleum Geology 122, 2020), indicating ages 1 to 3 Ma younger than the biostratigraphic estimates. The four MDA horizons provide a new time framework for sequence stratigraphic interpretation of the Miocene deposits as well as reconstruction of the basin-evolution model in the southwestern shelf of the Ulleung Basin.

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

A new quantitative method to validate the expression of homoeologous genes in polyploids - Keunhwa Kim; Eun Song Lee; Smita Mirsyad Warsadiharja; Junwoo Lee; Hye-yeong Kang; Ji In Jang; Yu Seon Chae; Soon Ju Park (Plant Biotechnology Reports, 2024)

A new neo-lignan from culture broth of Phellinus linteus and its dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Ji-Yul Kim; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Catalyst-recirculating system in steam explosion pretreatment for producing high-yield of xylooligosaccharides from oat husk - Myeong Rok Ahn; Song Wang; Jonghwa Kim; Sang-Mook You; Chan-Duck Jung; Hyolin Seong; June-Ho Choi; Sunkyu Park; In-Gyu Choi; Hoyong Kim (Carbohydrate Polymers, 2024)

T cell receptor clonotype in tumor microenvironment contributes to intratumoral signaling network in patients with colorectal cancer - In Hye Song; Seung-been Lee; Byung-Kwan Jeong; Jungwook Park; Honggeun Kim; GunHee Lee; Su Min Cha; Heejae Lee; Gyungyub Gong; Nak-Jung Kwon; Hee Jin Lee (Immunologic Research, 2024)

Evolution-aided improvement of the acid tolerance of Levilactobacillus brevis and its application in sourdough fermentation - Na Ree Han; Sora Yu; Jung A Byun; Eun Ju Yun; Seongwon Cheon; Seongbong Song; Sangmin Shim; In-Geol Choi; Sung-Ho Lee; Kyoung Heon Kim (Food Research International, 2024)

Consumer-driven characterization of healing foods using Q methodology and Q based sorting - Ki-Beom Song; Sébastien Lê; Haeng-Ran Kim; Seon-Mi Yoo; Min-Sook Kang; Han-Na Chu; In-Seon Hwang; Jae-Hee Hong (Food Quality and Preference, 2024)

Three undescribed dimeric ferulates from the culture broth of Phellinus linteus and their dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Won-Gi Seo; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Microbial valorization of fruit processing waste: opportunities, challenges, and strategies - In Jung Kim; Sujeong Park; Hyunjin Kyoung; Minho Song; Soo Rin Kim (Current Opinion in Food Science, 2024)

Maternal PM2.5 exposure is associated with preterm birth and gestational diabetes mellitus, and mitochondrial OXPHOS dysfunction in cord blood - Young-Ah You; Sunwha Park; Eunjin Kwon; Ye-Ah Kim; Young Min Hur; Ga In Lee; Soo Min Kim; Jeong Min Song; Man S. Kim; Young Ju Kim; Young-Han Kim; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2024)
Maternal exposure to fine particulate matter (PM 2.5 ) is associated with adverse pregnancy and neonatal health outcomes. To explore the mechanism, we performed mRNA sequencing of neonatal cord blood. From an ongoing prospective cohort, Air Pollution on Pregnancy Outcome (APPO) study, 454 pregnant women from six centers between January 2021 and June 2022 were recruited. Individual PM 2.5 exposure was calculated using a time-weighted average model. In the APPO study, age-matched cord blood samples from the High PM 2.5 (˃15 ug/m 3 ; n = 10) and Low PM 2.5 (≤ 15 ug/m 3 ; n = 30) groups were randomly selected for mRNA sequencing. After selecting genes with differential expression in the two groups ( p -value < 0.05 and log2 fold change > 1.5), pathway enrichment analysis was performed, and the mitochondrial pathway was analyzed using MitoCarta3.0. The risk of preterm birth (PTB) increased with every 5 µg/m 3 increase of PM 2.5 in the second trimester (odds ratio 1.391, p = 0.019) after adjusting for confounding variables. The risk of gestational diabetes mellitus (GDM) increased in the second (odds ratio 1.238, p = 0.041) and third trimester (odds ratio 1.290, p = 0.029), and entire pregnancy (odds ratio 1.295, p = 0.029). The mRNA-sequencing of cord blood showed that genes related to mitochondrial activity (FAM210B, KRT1, FOXO4, TRIM58, and FBXO7) and PTB-related genes (ADIPOR1, YBX1, OPTN, NFkB1, HBG2) were upregulated in the High PM 2.5 group. In addition, exposure to high PM 2.5 affected mitochondrial oxidative phosphorylation (OXPHOS) and proteins in the electron transport chain, a subunit of OXPHOS. These results suggest that exposure to high PM 2.5 during pregnancy may increase the risk of PTB and GDM, and dysregulate PTB-related genes. Alterations in mitochondrial OXPHOS by high PM 2.5 exposure may occur not only in preterm infants but also in normal newborns. Further studies with larger sample sizes are required.

Delineation of LNAPL plumes in a clay-rich site in Gyeongsangnam-do Province, South Korea: integration of geophysical survey data with borehole data and soil sampling information - Bitnarae Kim; In Seok Joung; Huieun Yu; Juyeon Jeong; Seo Young Song; Jeong-sul Son; Youngchul Yu; Jehyun Shin; Ho Young Jo; Man Jae Kwon; Myung Jin Nam (Environmental Monitoring and Assessment, 2024)

Efficient MAPbI3-based perovskite solar cells exceeding 21% efficiency via aging treatment - Dae Woo Kim; Young Wook Noh; Jongmin Han; Hye Seung Kim; Chung Hyeon Jang; Ji A. Hong; Sangmi Park; Min Hyeong Lee; Ye In Kim; Myoung Hoon Song (Chemical Engineering Journal, 2023)

Suppression of TBCK enhances TRAIL-mediated apoptosis by causing the inactivation of the akt signaling pathway in human renal carcinoma Caki-1 cells - Cho-Young Park; Ji-Hoon Jang; In-Hwan Song; Joo-Young Kim; Kyung-Oh Doh; Tae-Jin Lee (Genes & Genomics, 2023)

Sub-micron microplastics affect nitrogen cycling by altering microbial abundance and activities in a soil-legume system - Kanghee Kim; In-Gyu Song; Hakwon Yoon; June-Woo Park (Journal of Hazardous Materials, 2023)

Dual facet passivation of silver halometallate for eco-friendly silver bismuth sulfide near IR photodetector - Ashish Sharma; Hanjae Kim; Gunhee Kim; Jinhyeon Kang; Cheong Beom Lee; Sung Yong Bae; Hochan Song; Kyeounghak Kim; Jong Hyun Kim; In Hwan Jung; Dong-Won Kang; Jihoon Lee; et al. (Chemical Engineering Journal, 2023)

Microbial succession during button mushroom (Agaricus bisporus) production evaluated via high-throughput sequencing - Ga-Hee Ban; Jin-Hee Kim; Sun Ae Kim; Min Suk Rhee; Song Yi Choi; In Jun Hwang; Se-Ri Kim (Food Microbiology, 2023)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Biochemical responses and phytoremediation potential of Azolla imbricata (Roxb.) Nakai in water and nutrient media exposed to waste metal cutting fluid along with temperature and humidity stress - Sivakumar Subpiramaniyam; Sung-Chul Hong; Pyong-In Yi; Seong-Ho Jang; Jeong-Min Suh; Eun-Sang Jung; Je-Sung Park; Velmurugan Palanivel; Young-Chae Song; Lae-Hyeon Cho; Young-Hoon Park; Ji-Suk Kim (Journal of Hazardous Materials, 2023)

Chemical and morphological characterization by SEM–EDS of PM2.5 collected during winter in Ulaanbaatar, Mongolia - Ji-In Park; Min Sung Kim; Myoung Yeo; Mira Choi; Ji Yi Lee; Amgalan Natsagdorj; Changhyuk Kim; Mijung Song; Kyoung-Soon Jang (Atmospheric Environment, 2023)

A rice seed-specific glycine-rich protein OsDOR1 interacts with GID1 to repress GA signaling and regulates seed dormancy - Sooyeon Kim; Sun Mi Huh; Hay Ju Han; Gang Seob Lee; Yong-Sic Hwang; Mi Hyun Cho; Beom-Gi Kim; Ji Sun Song; Joo Hee Chung; Myung Hee Nam; Hyeonso Ji; Kyung-Hwan Kim; et al. (Plant Molecular Biology, 2023)

Sargassum horneri and Ascophyllum nodosum extracts enhance thermal tolerance and antioxidant activity of Neopyropia yezoensis - Sol Han; Hye-In Song; Ji-Sook Park; Youn-Jung Kim; Schery Umanzor; Charles Yarish; Jang K. Kim (Journal of Applied Phycology, 2023)

Assessment of sulfidated nanoscale zerovalent iron for in-situ remediation of cadmium-contaminated acidic groundwater at a zinc smelter - In-Gyu Song; Yu-Gyeong Kang; Jae-Hwan Kim; Hakwon Yoon; Woo Yong Um; Yoon-Seok Chang (Journal of Hazardous Materials, 2023)

Peptides inhibiting angiotensin-I-converting enzyme: Isolation from flavourzyme hydrolysate of Protaetia brevitarsis larva protein and identification - Jae Hoon Lee; Tae-Kyung Kim; Hae In Yong; Ji Yoon Cha; Kyung-Mo Song; Hyo Geun Lee; Jun-Geon Je; Min-Cheol Kang; Yun-Sang Choi (Food Chemistry, 2023)

Antiviral activity of canine interferon lambda 3 expressed using a recombinant adenovirus against canine coronavirus, canine parvovirus, and canine distemper virus - Dong-Hwi Kim; Sang-Hoon Han; Hyeon-Jeong Go; Da-Yoon Kim; Jae-Hyeong Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Veterinary Research Communications, 2022)

PKC-β modulates Ca2+ mobilization through Stim1 phosphorylation - Hye-Jin Song; In-Sook Jeon; Seung Ryul Kim; Kwan Sik Park; Jae-Won Soh; Kwang Youl Lee; Jae-Cheon Shin; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2022)
Background Calcium ions play a pivotal role in cell proliferation, differentiation, and migration. Under basal conditions, the calcium level is tightly regulated; however, cellular activation by growth factors increase the ion level through calcium pumps in the plasma membrane and endoplasmic reticulum for calcium signaling. Orai1 is a major calcium channel in the cell membrane of non-excitable cells, and its activity depends on the stromal interaction molecule 1 (Stim1). Several groups reported that the store-operated calcium entry (SOCE) can be modulated through phosphorylation of Stim1 by protein kinases such as extracellular signal-regulated kinase (ERK), protein kinase A (PKA), and p21-activated kinase (PAK). PKC is a protein kinase that is activated by calcium and diacylglycerol (DAG), but it remains unclear what role activated PKC plays in controlling the intracellular calcium pool. Objectives Here, we investigated whether PKC-β controls intracellular calcium dynamics through Stim1. Methods Several biochemical methods such as immune-precipitation, site directed mutagenesis, in vitro kinase assay were employed to investigate PKC interaction with and phosphorylation of Stim1. Intracellular calcium mobilization, via Stim1 mediated SOCE channel, were studied using in the presence of PKC activator or inhibitor under a confocal microscope. Results Our data demonstrate that PKC interacts with and phosphorylates Stim1 in vitro. phosphorylation of Stim1 at its C-terminal end appears to be important in the regulation of SOCE activity in HEK293 and HeLa cells. Additionally, transient intracellular calcium mobilization assays demonstrate that the SOCE activity was inhibited by PKC activators or activated by PKC inhibitors. Conclusion In sum, our data suggest a repressive role of PKC in regulating calcium entry through SOCE.

Characterization of non-solvent- and thermal-induced phase separation applied polycaprolactone/demineralized bone matrix scaffold for bone tissue engineering - Soo in Kim; Na Eun Kim; Sunjae Park; Joo Hee Choi; Younghun Lee; Gayeong Jeon; Jeong Eun Song; Gilson Khang (In vitro models, 2022)

Construction of full-length infectious cDNA clones of two Korean isolates of turnip mosaic virus breaking resistance in Brassica napus - Zheng-Xing Song; Eun-Young Seo; Wen-Xing Hu; Jong-Hyeon Jeong; Jae Sun Moon; Kang-Hee Kim; Won-Seob Eom; In-Sook Cho; John Hammond; Hyoun-Sub Lim (Archives of Virology, 2022)

Daldinans D‒G, new isoindolinone antioxidants isolated from the ascomycete Daldinia concentrica - Dae-Won Ki; Seong-Eun Kim; Ji-Yul Kim; Ja-Gyeong Song; Byung Soon Hwang; In-Kyoung Lee; Bong-Sik Yun (Journal of Natural Medicines, 2022)

Neferine increases sensitivities to multiple anticancer drugs via downregulation of Bcl-2 expression in renal cancer cells - Eun-Ae Kim; Ji Hoon Jang; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Ho-Yong Sohn; Tae-Jin Lee (Genes & Genomics, 2022)

The optimal standard protocols for whole-genome sequencing of antibiotic-resistant pathogenic bacteria using third-generation sequencing platforms - Tae-Min La; Ji-hoon Kim; Taesoo Kim; Hong-Jae Lee; Yoonsuk Lee; Hyunjin Shin; Yongjun Song; Gyuhee Ahn; Won Hur; Joong-Bok Lee; Seung-Yong Park; In-Soo Choi; et al. (Molecular & Cellular Toxicology, 2021)

Lactucin induces apoptosis through reactive oxygen species-mediated BCL-2 and CFLARL downregulation in Caki-1 cells - Ji Hoon Jang; Cho-Young Park; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Chuleui Jung; Ho-Yong Sohn; Tae-Jin Lee (Genes & Genomics, 2021)

Overexpression of Arabidopsis thaliana blue-light inhibitor of cryptochromes 1 gene alters plant architecture in soybean - Hyun Suk Cho; Yoon Jeong Lee; Hye Jeong Kim; Moon-Young Park; Wan Woo Yeom; Ji Hyeon Song; In Ah Kim; Seong-Hyeon Kim; Jeong-Il Kim; Young-Soo Chung (Plant Biotechnology Reports, 2021)

Temporal variation of sulfate concentration in PM2.5 and major factors enhancing sulfate concentration in the atmosphere of Seoul, Korea - Na Kyung Kim; In Sun Kim; In Ho Song; Seung Myung Park; Hyung Bae Lim; Yong Pyo Kim; Hye Jung Shin; Ji Yi Lee (Air Quality, Atmosphere & Health, 2021)

Fucoxanthin biosynthesis has a positive correlation with the specific growth rate in the culture of microalga Phaeodactylum tricornutum - Do Yeon Kwon; Trang Thi Vuong; Jaeyoung Choi; Taek Sung Lee; Jae-In Um; Song Yi Koo; Keum Taek Hwang; Sang Min Kim (Journal of Applied Phycology, 2021)

Biological activities and chemical components of Potentilla kleiniana Wight & Arn - Song Hua Xuan; In Ki Hong; Yun Ju Lee; Ji Woong Kim; Soo Nam Park (Natural Product Research, 2020)

T cell receptor repertoires of ex vivo–expanded tumor-infiltrating lymphocytes from breast cancer patients - In Ah Park; Hajar Rajaei; Young-Ae Kim; Hyeonjin Lee; Heejae Lee; Jeong-Han Seo; Sun-Hee Heo; In Hye Song; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2020)

High-throughput phenotyping platform for analyzing drought tolerance in rice - Song Lim Kim; Nyunhee Kim; Hongseok Lee; Eungyeong Lee; Kyeong-Seong Cheon; Minsu Kim; JeongHo Baek; Inchan Choi; Hyeonso Ji; In Sun Yoon; Ki-Hong Jung; Taek-Ryoun Kwon; et al. (Planta, 2020)
Main conclusion A new imaging platform was constructed to analyze drought-tolerant traits of rice. Rice was used to quantify drought phenotypes through image-based parameters and analyzing tools. Abstract Climate change has increased the frequency and severity of drought, which limits crop production worldwide. Developing new cultivars with increased drought tolerance and short breeding cycles is critical. However, achieving this goal requires phenotyping a large number of breeding populations in a short time and in an accurate manner. Novel cutting-edge technologies such as those based on remote sensors are being applied to solve this problem. In this study, new technologies were applied to obtain and analyze imaging data and establish efficient screening platforms for drought tolerance in rice using the drought-tolerant mutant osphyb . Red–Green–Blue images were used to predict plant area, color, and compactness. Near-infrared imaging was used to determine the water content of rice, infrared was used to assess plant temperature, and fluorescence was used to examine photosynthesis efficiency. DroughtSpotter technology was used to determine water use efficiency, plant water loss rate, and transpiration rate. The results indicate that these methods can detect the difference between tolerant and susceptible plants, suggesting their value as high-throughput phenotyping methods for short breeding cycles as well as for functional genetic studies of tolerance to drought stress.

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

Integration of transcriptomics, proteomics and metabolomics identifies biomarkers for pulmonary injury by polyhexamethylene guanidine phosphate (PHMG-p), a humidifier disinfectant, in rats - Jung Dae Lee; Hyang Yeon Kim; Keunsoo Kang; Hye Gwang Jeong; Mi-Kyung Song; In Hwan Tae; Su Hyun Lee; Hae Ri Kim; Kyuhong Lee; Sehyun Chae; Daehee Hwang; Suhkmann Kim; et al. (Archives of Toxicology, 2020)

Changes in soil properties for 6 years of using the freshwater snail (Ampullaria tischbeini Dohrn) in a reclaimed sodic soil - Jong-Song Jo; Song-Ho Pak; Chol-Ho Ri; Song-Ok Cha; Gwang-Rim Kim; Chon-Il Ri; In-Song Kim (Journal of Soils and Sediments, 2020)

Orexin A-induced inhibition of leptin expression and secretion in adipocytes reducing plasma leptin levels and hypothalamic leptin resistance - Su-Kyung Shin; Seung-Eun Song; Jin Uk Oh; Meeyul Hwang; Hyun-Woo Cho; Jae-Hoon Bae; Seung-Soon Im; Jee-In Kim; Dae-Kyu Song (Pflügers Archiv - European Journal of Physiology, 2019)

Retained or altered expression of major histocompatibility complex class I in patient-derived xenograft models in breast cancer - In Hye Song; Young-Ae Kim; Hyeonjin Lee; Hye Seon Park; In Ah Park; Chan Kyu Sim; Myeong Sup Lee; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2019)

A comparative evaluation of BACT/ALERT FA PLUS and FN PLUS blood culture bottles and BD BACTEC Plus Aerobic and Anaerobic blood culture bottles for antimicrobial neutralization - Yousun Chung; In-Hee Kim; Minje Han; Hyun Soo Kim; Han-Sung Kim; Wonkeun Song; Jae-Seok Kim (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Exploring the Probiotic and Compound Feed Fermentative Applications of Lactobacillus plantarum SK1305 Isolated from Korean Green Chili Pickled Pepper - Kai-Min Niu; Damini Kothari; Sang-Buem Cho; Sung-Gu Han; In-Geun Song; Sam-Churl Kim; Soo-Ki Kim (Probiotics and Antimicrobial Proteins, 2019)

Multidrug-resistant Acinetobacter baumannii infection in lung transplant recipients: risk factors and prognosis - Dong Hyun Oh; Yong Chan Kim; Eun Jin Kim; In Young Jung; Su Jin Jeong; Song Yee Kim; Moo Suk Park; Anes Kim; Jin Gu Lee; Hyo Chae Paik (Infectious Diseases, 2019)

PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2019)
Impaired neurogenesis has been associated with several brain disorders, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The role of peroxiredoxin 6 (PRDX6) in neurodegenerative diseases is very controversial. To demonstrate the role of PRDX6 in neurogenesis, we compared the neurogenesis ability of PRDX6-overexpressing transgenic (Tg) mice and wild-type mice and studied the involved molecular mechanisms. We showed that the neurogenesis of neural stem cells (NSCs) and the expression of the marker protein were lower in PRDX6 Tg-mice than in wild-type mice. To determine the factors involved in PRDX6-related neural stem cell impairment, we performed a microarray experiment. We showed that the expression of WDFY1 was dramatically decreased in PRDX6-Tg mice. Moreover, WDFY1 siRNA decreases the differentiation ability of primary neural stem cells. Interestingly, WDFY1 reportedly recruits the signaling adaptor TIR-domain-containing adapter-inducing interferon-β (TRIF) to toll-like receptors (TLRs); thus, we showed the relationship among TLRs, PRDX6, and WDFY1. We showed that TLR4 was dramatically reduced in PRDX6 Tg mice, and reduced TLR4 expression and neurogenesis was reversed by the introduction of WDFY1 plasmid in the neural stem cells from PRDX6 Tg mice. This study indicated that PRDX6 inhibits the neurogenesis of neural precursor cells through TLR4-dependent downregulation of WDFY1 and suggested that the inhibitory effect of PRDX6 on neurogenesis play a role in the development of neurodegenerative diseases in the PRDX6 overexpressing transgenic mice.

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Differential regional infarction, neuronal loss and gliosis in the gerbil cerebral hemisphere following 30 min of unilateral common carotid artery occlusion - Ji Hyeon Ahn; Minah Song; Hyunjung Kim; Tae-Kyeong Lee; Cheol Woo Park; Young Eun Park; Jae-Chul Lee; Jun Hwi Cho; Young-Myeong Kim; In Koo Hwang; Moo-Ho Won; Joon Ha Park (Metabolic Brain Disease, 2019)

Severe Cardiomyopathy Due to Arthroprosthetic Cobaltism: Report of Two Cases with Different Outcomes - Hyo-In Choi; Jung Ae Hong; Min-Seok Kim; Sang Eun Lee; Sung-Ho Jung; Pil Whan Yoon; Joon Seon Song; Jae-Joong Kim (Cardiovascular Toxicology, 2019)

Inoculum effect of methicillin-susceptible Staphylococcus aureus against broad-spectrum beta-lactam antibiotics - Kyoung-Ho Song; Sook-In Jung; Shinwon Lee; Sohee Park; Eu Suk Kim; Kyung-Hwa Park; Wan Beom Park; Pyoeng Gyun Choe; Young Keun Kim; Yee Gyung Kwak; Yeon-Sook Kim; Hee-Chang Jang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Factors affecting the public awareness and behavior on antibiotic use - Kyungmin Huh; Doo Ryeon Chung; So Hyun Kim; Sun Young Cho; Young Eun Ha; Cheol-In Kang; Kyong Ran Peck; Jae-Hoon Song (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Evidence of hepatitis E virus infection in specific pathogen-free rabbits in Korea - Sang-Hoon Han; Byung-Joo Park; Hee-Seop Ahn; Yong-Hyun Kim; Hyeon-Jeong Go; Dong-Hwi Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Virus Genes, 2018)

Expression of anthocyanin biosynthesis-related genes reflects the peel color in purple tomato - Song-I Kang; Md Abdur Rahim; Khandker Shazia Afrin; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2018)

Gender affects prognosis of methicillin-resistant Staphylococcus aureus bacteremia differently depending on the severity of underlying disease - Chang Kyung Kang; Yee Gyung Kwak; Youngmi Park; Kyoung-Ho Song; Eu Suk Kim; Sook-In Jung; Kyung-Hwa Park; Wan Beom Park; Nam Joong Kim; Young Keun Kim; Hee-Chang Jang; Shinwon Lee; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Development of an Observation Processing Package for Data Assimilation in KIAPS - Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Ji-Hyun Ha; Hyo-Jong Song; In-Hyuk Kwon; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of an Operational Hybrid Data Assimilation System at KIAPS - In-Hyuk Kwon; Hyo-Jong Song; Ji-Hyun Ha; Hyoung-Wook Chun; Jeon-Ho Kang; Sihye Lee; Sujeong Lim; Youngsoon Jo; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Seoleun Shin; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Multi-resolution Hybrid Data Assimilation Core on a Cubed-sphere Grid (HybDA) - Hyo-Jong Song; Ji-Hyun Ha; In-Hyuk Kwon; Junghan Kim; Jihye Kwun (Asia-Pacific Journal of Atmospheric Sciences, 2018)

The Korean Integrated Model (KIM) System for Global Weather Forecasting - Song-You Hong; Young Cheol Kwon; Tae-Hun Kim; Jung-Eun Esther Kim; Suk-Jin Choi; In-Hyuk Kwon; Junghan Kim; Eun-Hee Lee; Rae-Seol Park; Dong-Il Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Potential silver nanoparticles migration from commercially available polymeric baby products into food simulants - Jeong In Choi; Song Ji Chae; Jung Min Kim; Jae Chun Choi; Se Jong Park; Hee Ju Choi; Hojae Bae; Hyun Jin Park (Food Additives & Contaminants: Part A, 2018)

Fabrication of Fe/Mn oxide composite adsorbents for adsorptive removal of zinc and phosphate - Chul-Min Chon; Dong-Wan Cho; In-Hyun Nam; Jae-Gon Kim; Hocheol Song (Journal of Soils and Sediments, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Endogenous TRPV4 Expression of a Hybrid Neuronal Cell Line N18D3 and Its Utilization to Find a Novel Synthetic Ligand - Sungjae Yoo; Seung-In Choi; Seul Lee; Jiho Song; Chungmi Yang; Sangsu Bang; Seung Up Kim; Kyung Hoon Min; Sun Wook Hwang (Journal of Molecular Neuroscience, 2017)

Whole-genome sequence analysis of Zika virus, amplified from urine of traveler from the Philippines - Se Hun Gu; Dong Hyun Song; Daesang Lee; Jeyoun Jang; Min Young Kim; Jaehun Jung; Koung In Woo; Mirang Kim; Woong Seog; Hong Sang Oh; Byung Seop Choi; Jong-Seong Ahn; et al. (Virus Genes, 2017)

Data management for plant phenomics - Song-Lim Kim; Nita Solehati; In-Chan Choi; Kyung-Hwan Kim; Taek-Ryoun Kwon (Journal of Plant Biology, 2017)

TSG-6 secreted by mesenchymal stem cells suppresses immune reactions influenced by BMP-2 through p38 and MEK mitogen-activated protein kinase pathway - Soyoun Um; Hui Young Kim; Joo-Hee Lee; In-Seok Song; Byoung Moo Seo (Cell and Tissue Research, 2017)

Simultaneous estimation of saponin contents from soybean seed using Fourier transform infrared spectroscopy and high-performance liquid chromatography analysis - Myung Suk Ahn; Eun Yee Jie; Seung Yeob Song; Hong Sig Kim; In-Jung Kim; Suk Weon Kim (Plant Biotechnology Reports, 2016)

Genetic characteristics of highly pathogenic H5N8 avian influenza viruses isolated from migratory wild birds in South Korea during 2014-2015 - Young-Jae Si; Won Suk Choi; Young-Il Kim; In-Won Lee; Hyeok-Il Kwon; Su-Jin Park; Eun-Ha Kim; Se mi Kim; Jin-Jung Kwon; Min-Suk Song; Chul-Joong Kim; Young-Ki Choi (Archives of Virology, 2016)

Local injection of granulocyte-colony stimulating factor accelerates wound healing in a rat excisional wound model - Guang-Yin Shen; In-Hwa Park; Yi-Sun Song; Hyun-Woo Joo; Yonggu Lee; Jeong-Hun Shin; Kyung-Soo Kim; Hyuck Kim (Tissue Engineering and Regenerative Medicine, 2016)

Molecular analyses of H3N2 canine influenza viruses isolated from Korea during 2013–2014 - EunJung Lee; Eun-Ju Kim; Bo-Hye Kim; Jae-Young Song; In-Soo Cho; Yeun-Kyung Shin (Virus Genes, 2016)

Transgenic Turfgrasses Expressing Hyperactive Ser599Ala Phytochrome A Mutant Exhibit Abiotic Stress Tolerance - Mayank Anand Gururani; Markkandan Ganesan; In-Ja Song; Yunjeong Han; Jeong-Il Kim; Hyo-Yeon Lee; Pill-Soon Song (Journal of Plant Growth Regulation, 2016)

Inhibitory effect of snake venom toxin on NF-κB activity prevents human cervical cancer cell growth via increase of death receptor 3 and 5 expression - Hye Lim Lee; Mi Hee Park; Ji Eun Hong; Dae Hwan Kim; Ji Young Kim; Hyen Ok Seo; Sang-Bae Han; Joo Hee Yoon; Won Hyoung Lee; Ho Sueb Song; Ji In Lee; Ung Soo Lee; et al. (Archives of Toxicology, 2016)

Echinochrome A regulates phosphorylation of phospholamban Ser16 and Thr17 suppressing cardiac SERCA2A Ca2+ reuptake - Hyoung Kyu Kim; Jae Boum Youm; Seung Hun Jeong; Sung Ryul Lee; In-Sung Song; Tae Hee Ko; Julius Ryan Pronto; Kyung Soo Ko; Byoung Doo Rhee; Nari Kim; Bernd Nilius; Natalia P. Mischchenko; et al. (Pflügers Archiv - European Journal of Physiology, 2015)

Abundance and Distribution Characteristics of Microplastics in Surface Seawaters of the Incheon/Kyeonggi Coastal Region - Doo-Hyeon Chae; In-Sung Kim; Seung-Kyu Kim; Young Kyoung Song; Won Joon Shim (Archives of Environmental Contamination and Toxicology, 2015)

Erratum to: Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2015)

Monthly metabolic changes and PLS prediction of carotenoid content of citrus fruit by combined Fourier transform infrared spectroscopy and quantitative HPLC analysis - Suk Weon Kim; Myung Suk Ahn; Yong Kook Kwon; Seung Yeob Song; Jae Kwang Kim; Sun-Hwa Ha; In-Jung Kim; Jang R. Liu (Plant Biotechnology Reports, 2015)

Coix seed extract attenuates the high-fat induced mouse obesity via PPARγ and C/EBPα a downregulation - Eun-Kyeong Choi; Yu Jeong Cho; Hea Jung Yang; Ki-Suk Kim; In-Seung Lee; Jong-Chan Jang; Kang-Hoon Kim; Ji Hyun Bang; Yumi Kim; Se Hoon Kim; Young-Hwan Cho; Na Young Yoon; et al. (Molecular & Cellular Toxicology, 2015)

Protective effect of a novel herbmedicine, Hepad, on apoptosis of SH-SY5Y cells and a rat model of Parkinson’s disease - Seung Yeop Baek; Na Rae Lee; Da Hye Kim; Ayoung Gu; Seong Yeol Kim; Dae-Yong Song; Dong-Hee Kim; Hak Joo Choi; Byung-Jun Park; In Sik Kim (Molecular & Cellular Toxicology, 2015)

Glycan structure and serum half-life of recombinant CTLA4Ig, an immunosuppressive agent, expressed in suspension-cultured rice cells with coexpression of human β1,4-galactosyltransferase and human CTLA4Ig - Seung Hoon Kang; Hahn Sun Jung; Song Jae Lee; Cheon Ik Park; Sang Min Lim; Heajin Park; Byung Sun Kim; Kwang Heum Na; Gyeong Jin Han; Jae Woo Bae; Hyun Joo Park; Keuk Chan Bang; et al. (Glycoconjugate Journal, 2015)

Molecular evolution of kobuviruses in cats - Yoon-Young Cho; Seong-In Lim; Yong Kwan Kim; Jae-Young Song; Joong-Bok Lee; Dong-Jun An (Archives of Virology, 2015)

B7-H4 downregulation induces mitochondrial dysfunction and enhances doxorubicin sensitivity via the cAMP/CREB/PGC1-α signaling pathway in HeLa cells - Hyoung Kyu Kim; In-Sung Song; Sun Young Lee; Seung Hun Jeong; Sung Ryul Lee; Hye Jin Heo; Vu Thi Thu; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Dae Hun Jeong; Young Nam Kim; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

Polyphenols and antioxidant capacity of a spontaneous reddish mutant in Satsuma mandarin, Shinheungri - Min Young Kim; In-Jung Kim; Soon Jae Im; Ji Hye Kim; Ji-Man Heo; Seung-Yeob Song; Jung Hyun Kim; Seo Hyun Moon; Seongbeom Cho (Natural Product Research, 2014)

Comparative transcriptomic analysis to identify differentially expressed genes in fat tissue of adult Berkshire and Jeju Native Pig using RNA-seq - Simrinder Singh Sodhi; Won Cheoul Park; Mrinmoy Ghosh; Jin Nam Kim; Neelesh Sharma; Kwang Yun Shin; In Cheol Cho; Youn Chul Ryu; Sung Jong Oh; Sung Hoon Kim; Ki-Duk Song; Sang Pyo Hong; et al. (Molecular Biology Reports, 2014)

Transcriptome analysis of mistletoe (Viscum album) haustorium development - Suk Min Ko; Yong Kook Kwon; Jong Hyun Kim; In-Ja Song; Hyo-Yeon Lee; Dong-Woog Choi; Jang R. Liu; Suk Weon Kim (Horticulture, Environment, and Biotechnology, 2014)

Dioscin induces caspase-independent apoptosis through activation of apoptosis-inducing factor in breast cancer cells - Eun-Ae Kim; Ji-Hoon Jang; Yun-Han Lee; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Suji Kim; Ho-Yong Sohn; Tae-Jin Lee (Apoptosis, 2014)

Antimicrobial peptides in the centipede Scolopendra subspinipes mutilans - Won Gi Yoo; Joon Ha Lee; Younhee Shin; Jae-Young Shim; Myunghee Jung; Byeong-Chul Kang; Jaedon Oh; Jiyeon Seong; Hak Kyo Lee; Hong Sik Kong; Ki-Duk Song; Eun-Young Yun; et al. (Functional & Integrative Genomics, 2014)

3,4,5-Trihydroxycinnamic acid inhibits lipopolysaccharide (LPS)-induced inflammation by Nrf2 activation in vitro and improves survival of mice in LPS-induced endotoxemia model in vivo - Jae-Won Lee; Chang Jun Bae; Yong-Jun Choi; Song-In Kim; Yong-Soo Kwon; Hee Jae Lee; Sung-Soo Kim; Wanjoo Chun (Molecular and Cellular Biochemistry, 2014)

Halapricum salinum gen. nov., sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - Hye Seon Song; In-Tae Cha; Kyung June Yim; Hae-Won Lee; Dong-Wook Hyun; Sung-Jae Lee; Sung-Keun Rhee; Kil-Nam Kim; Daekyung Kim; Jong-Soon Choi; Myung-Ji Seo; Hak-Jong Choi; et al. (Antonie van Leeuwenhoek, 2014)

Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2014)

Halobellus rufus sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Myung-Ji Seo; Daekyung Kim; Jong-Soon Choi; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; et al. (Antonie van Leeuwenhoek, 2014)

Halorubrum halophilum sp. nov., an extremely halophilic archaeon isolated from a salt-fermented seafood - Kyung June Yim; In-Tae Cha; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Sung-Jae Lee; Young-Do Nam; Dong-Wook Hyun; Jin-Woo Bae; Sung-Keun Rhee; Myung-Ji Seo; Jong-Soon Choi; et al. (Antonie van Leeuwenhoek, 2014)

Halococcus sediminicola sp. nov., an extremely halophilic archaeon isolated from a marine sediment - Kyung June Yim; In-Tae Cha; Tae Woong Whon; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Young-Do Nam; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; Jong-Soon Choi; Myung-Ji Seo; et al. (Antonie van Leeuwenhoek, 2014)

Comparative study on the fauna composition of intertidal invertebrates between natural and artificial substrata in the northeastern coast of Jeju Island - Jae-Hoon Cha; Kwang-Bae Kim; Ji-Na Song; In-Soo Kim; Jeong-Bin Seo; Chul-Hwi Kwoun (Ocean Science Journal, 2013)

Dietary aflatoxin B1 intake, genetic polymorphisms of CYP1A2, CYP2E1, EPHX1, GSTM1, and GSTT1, and gastric cancer risk in Korean - Sang-Yong Eom; Dong-Hyuk Yim; Yanwei Zhang; Jung-Kuk Yun; Sun In Moon; Hyo-Yung Yun; Young-Jin Song; Sei-Jin Youn; Taisun Hyun; Joo-Seung Park; Byung Sik Kim; Jong-Young Lee; et al. (Cancer Causes & Control, 2013)

Neural substrates of acupuncture in the modulation of cravings induced by smoking-related visual cues: an FMRI study - O-Seok Kang; Song-Yi Kim; Geon-Ho Jahng; Hackjin Kim; Jong-Woo Kim; Sun-Yong Chung; Jun-Won Kim; Seung-In Yang; Hi-Joon Park; Hyejung Lee; Younbyoung Chae (Psychopharmacology, 2013)

Immune responses in mice vaccinated with virus-like particles composed of the GP5 and M proteins of porcine reproductive and respiratory syndrome virus - Hae-Mi Nam; Kyung-Sil Chae; Young-Jo Song; Nak-Hyung Lee; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Kun-Ho Seo; Sang-Moo Kang; Min-Chul Kim; In-Soo Choi (Archives of Virology, 2013)

Comparative analysis of physicochemicals and antioxidative properties in new red rice (Oryza sativa L. cv. Gunganghongmi) - Woo Duck Seo; Jun Young Kim; You-Chun Song; Jun-Hyun Cho; Ki Chang Jang; Sang-Ik Han; Ji-Eun Ra; Seong-Hwan Oh; Hyeon-Jung Kang; Byung-Joo Kim; Nam-In Baek; Rak-Hun Jeong; et al. (Journal of Crop Science and Biotechnology, 2013)

Non-genomic effect of glucocorticoids on cardiovascular system - Sung Ryul Lee; Hyoung Kyu Kim; Jae Boum Youm; Louise Anne Dizon; In Sung Song; Seung Hun Jeong; Dae Yun Seo; Kyoung Soo Ko; Byoung Doo Rhee; Nari Kim; Jin Han (Pflügers Archiv - European Journal of Physiology, 2012)

Effects of Serum Calcium and Magnesium on Heart Rate Variability in Adult Women - Yeong-Hoon Kim; Kyu-In Jung; Chan-Hee Song (Biological Trace Element Research, 2012)

Erratum to: Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekkhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

Associations of Zinc and Copper Levels in Serum and Hair with Sleep Duration in Adult Women - Chan-Hee Song; Yeong-Hoon Kim; Kyu-In Jung (Biological Trace Element Research, 2012)

Toxicogenomic comparison of multi-wall carbon nanotubes (MWCNTs) and asbestos - Jin Sik Kim; Kyung Seuk Song; Jin Kyu Lee; Young C. Choi; In Seok Bang; Chang Soo Kang; Il Je Yu (Archives of Toxicology, 2012)

Gene expression analysis identifies DNA damage-related markers of benzo[a]pyrene exposure in HepG2 human hepatocytes - Mi-Kyung Song; Ji-Seong Yoon; Mee Song; Han-Seam Choi; Chan-Young Shin; Youn-Jung Kim; Woo-In Ryu; Hyo-Sun Lee; Jae-Chun Ryu (Toxicology and Environmental Health Sciences, 2012)

Hepatoprotection of different water extracts from Acer tegmentosum M. on CCl4-induced acute hepatotoxicity in mice: comparative efficacies between the extracts of boughs, twigs, and leaves - Kwang-Yong Shim; Dong-Heui Kim; Soon-Bong Song; Xu-Feng Qi; Yang-Suk Yoon; Hyun-Soo Kim; Jong-In Lee; Hwa-Eun Oh; Soo-Ki Kim; Kyu-Jae Lee (Molecular & Cellular Toxicology, 2011)

Expression of the protective antigen for PEDV in transgenic duckweed, Lemna minor - Suk-Min Ko; Hyeon-Jin Sun; Myung Jin Oh; In-Ja Song; Min-Jae Kim; Hyun-Sook Sin; Chang-Hyo Goh; Yong-Woo Kim; Pyung-Ok Lim; Hyo-Yeon Lee; Suk Weon Kim (Horticulture, Environment, and Biotechnology, 2011)

The effects of benzene and toluene on leukotactin-1-induced migration of EoL-1 cells - Bo Bae Song; Eun Ju Yang; Bo-Mi Kim; Ji-Sook Lee; Chi-Young Yun; Yang-Bin Im; In Sik Kim (Molecular & Cellular Toxicology, 2011)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

Molecular characterization of rotavirus diarrhea among children in South Korea: detection of an unusual G11 strain - Jung Ok Shim; In Hyuk Baek; Van Phan Le; Eun-Mi Ko; Won-Seok Seok; Young Uh; Ja Kyoung Kim; Sung Yeon Ahn; Hyeon Soo Lee; Eell Ryoo; So-Yeon Shim; Wonkeun Song; et al. (Archives of Virology, 2011)

Extract of Poncirus trifoliata fruit reduces elevated serum IgE concentrations in chemically induced allergic model mice - Hyun Jung Park; Jong Bo Kim; In Song Han; Jin Hoi Kim; Bokyung Kim; Sung-Ho Kang; Ho-Sung Jung; Sang Ho Moon; Si Heung Sung; Hyuk Song (Horticulture, Environment, and Biotechnology, 2011)

A possible association of EMID2 polymorphisms with aspirin hypersensitivity in asthma - Charisse Flerida A. Pasaje; Jeong-Hyun Kim; Byung-Lae Park; Hyun Sub Cheong; Mi-Kyeong Kim; Inseon S. Choi; Sang Heon Cho; Chein-Soo Hong; Yong Won Lee; Jae-Young Lee; In Song Koh; Tae-Joon Park; et al. (Immunogenetics, 2011)

Transformation of carotenoid biosynthetic genes using a micro-cross section method in kiwifruit (Actinidia deliciosa cv. Hayward) - Misun Kim; Seong-Cheol Kim; Kwan Jeong Song; Ho Bang Kim; In-Jung Kim; Eun-Young Song; Seung-Jong Chun (Plant Cell Reports, 2010)

Effect of dietary nutrient composition on the growth of olive flounder (Paralichthys olivaceus) with different feeding regimes - Sung Hwoan Cho; Choong-Il Kim; In-Seok Park; Young-Chae Song; Chankeun Park; Kyung-Duck Kim (Fish Physiology and Biochemistry, 2010)

Effects of glyceollin I on vascular contraction in rat aorta - Min-Ji Song; Inji Baek; Su Bun Jeon; Minchul Seo; Yong-Hoon Kim; Song Cui; Yeon-Shin Jeong; In-Jung Lee; Dong Hyun Shin; Young Hyun Hwang; In Kyeom Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Breeding of four-leaf white clover (Trifolium repens L.) through 60Co gamma-ray irradiation - In-Ja Song; Hong-Gyu Kang; Ji-Yeon Kang; Hae-Deun Kim; Tae-Woong Bae; Si-Young Kang; Pyung-Ok Lim; Taiji Adachi; Hyo-Yeon Lee (Plant Biotechnology Reports, 2009)

A novel mutation in Hr causes abnormal hair follicle morphogenesis in hairpoor mouse, an animal model for Marie Unna Hereditary Hypotrichosis - In Cheol Baek; Jeong Ki Kim; Kyu-Hyuk Cho; Dal-Sun Cha; Jae-Woo Cho; Jong Keun Park; Chang-Woo Song; Sungjoo Kim Yoon (Mammalian Genome, 2009)

Anti-inflammatory effects of talosin A via inhibition of NF-kappaB activation in lipopolysaccharide-stimulated RAW264.7 cells - Youn-Hwan Hwang; Myoung-Seok Kim; In-Bae Song; Jong-Hwan Lim; Byung-Kwon Park; Hyo-In Yun (Biotechnology Letters, 2009)

Buprederm™, a New Transdermal Delivery System of Buprenorphine: Pharmacokinetic, Efficacy and Skin Irritancy Studies - In Park; Dongwon Kim; Jindeog Song; Chang Hoon In; Seung-Wei Jeong; Sang Hun Lee; Bumchan Min; Dongho Lee; Sun-Ok Kim (Pharmaceutical Research, 2008)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Mechanism by whichBacillus-Derived 2-Aminobenzoic acid inhibits the growth ofArabidopsis thaliana Roots - Lam Hoang; Kyung Sik Song; In Koo Rhee; Jeong Hoe Kim; Sangman Lee (Journal of Plant Biology, 2007)

Vegetation of Barton Peninsula in the neighbourhood of King Sejong Station (King George Island, maritime Antarctic) - Ji Hee Kim; In-Young Ahn; Kyu Song Lee; Hosung Chung; Han-Gu Choi (Polar Biology, 2007)

Ca2+ and Cu2+ supplementation increases mannitol production by Candida magnoliae - Jung-Kul Lee; Deok-Kun Oh; Hee-Yeol Song; In-Won Kim (Biotechnology Letters, 2007)

Brain-derived neurotrophic factor modulates the dopaminergic network in the rat retina after axotomy - Eun-Jin Lee; Myoung-Chul Song; Hyun-Ju Kim; Eun-Jin Lim; In-Beom Kim; Su-Ja Oh; Jung-IL Moon; Myung-Hoon Chun (Cell and Tissue Research, 2005)

Growth promotion of red pepper plug seedlings and the production of gibberellins by Bacillus cereus, Bacillus macroides and Bacillus pumilus - Gil-Jae Joo; Young-Mog Kim; In-Jung Lee; Kyung-Sik Song; In-Koo Rhee (Biotechnology Letters, 2004)

Changes in gene expression during hairy root formation byAgrobacterium rhizogenes infection in ginseng - Hwa -Jee Chung; In Sook Cho; Jee -Hyub Kim; Dong Su In; Cheol Goo Hur; Ji Sook Song; Sung Sick Woo; Dong -Woog Choi; Jang Ryol Liu (Journal of Plant Biology, 2003)

Kidney-Specific Activity of the Bovine Uromodulin Promoter - Hun-Taek Kim; In-Young Song; Jorge Piedrahita (Transgenic Research, 2003)

Comparison of 16S rDNA analysis and rep-PCR genomic fingerprinting for molecular identification of Yersinia pseudotuberculosis - Wonyong Kim; Mi-Ok Song; Wonkeun Song; Ki-Jung Kim; Sang-In Chung; Chul-Soon Choi; Yong-Ha Park (Antonie van Leeuwenhoek, 2003)

Karyotypes of three somaclonal variants and wild plants ofAllium tuberosum by bicolor FISH - Geum-Sook Do; Bong-Bo Seo; Jae-Hong Pak; In-Sun Kim; Seung-Dal Song (Journal of Plant Biology, 2000)

Ultrastructure of leaves in C4 Cyperus iria and C3 Carex siderosticta - In Sun Kim; Jae-Hong Pak; Bong-Bo Seo; Seung-Dal Song (Journal of Plant Biology, 1999)

Analysis of somaclonal variation through tissue culture and chromosomal localization of rDNA sites by fluorescent in situ hybridization in wild Allium tuberosum and a regenerated variant - Geum-Sook Do; Bong-Bo Seo; Jong-Min Ko; Seon-Hee Lee; Jae-Hong Pak; In-Sun Kim; Seung-Dal Song (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Ultrastructural aspects of leaves inFestuca ovina andPoa sphondylodes (C-3 Poaceae) - In Sun Kim; Jae-Hong Pak; Bong-Bo Seo; Seung-Dal Song (Journal of Plant Biology, 1998)

Decrease in carbamylation of rubisco by high CO2 concentration is due to decrease of rubisco activase in kidney bean - Kwang Soo Roh; In Seob Kim; Byung Weon Kim; Jong Suk Song; Hwa Sook Chung; Seung Dal Song (Journal of Plant Biology, 1997)